Federal Inland Revenue Service and Taxation Reforms in Democratic Nigeria - Okauru, Ifueko Omoigui (Book collections on Project MUSE., 2012)
In line with the federal structure of the Nigerian State, tax administration in the country is multi-tiered. The Federal Inland Revenue Service is responsible for assessing, collecting and accounting for tax and other revenues accruing to the Federal Government. The States Boards of Internal Revenue and the Local Government Revenue Committees perform similar functions at the State and Local Government levels respectively. This book attempts to chronicle the changes that have been taking place within the Federal Inland Revenue Service since 2004 and how these activities have contributed to the reforms in the Nigerian tax system. In terms of value, the book facilitates an understanding of the role played by the Service; its staff and stakeholders in repositioning the Nigerian tax system. It is an essential reference material for everyone that seeks an understanding of the processes that underscore the ongoing changes in the Nigerian tax system.